LONG-TERM RESPIRATORY SEQUELAE FOLLOWING ACUTE BRONCHIOLITIS IN CHILDREN: POST-VIRAL WHEEZING AND ASTHMA RISK (International journal of medical sciences, 2025)
Background: Acute bronchiolitis in infancy is the most common cause of hospitalization worldwide. However, its impact extends beyond the acute phase, with a significant proportion of children developing recurrent post-viral wheezing and asthma in later childhood. Objective: This article aims to evaluate the long-term respiratory sequelae of acute bronchiolitis, focusing on the stratification of risk for developing bronchial asthma versus transient wheezing, and the differential roles of viral pathogens (RSV vs. Rhinovirus). Methods: A systematic review of longitudinal birth cohort studies and clinical trials published between 2018 and 2024 was conducted. Key databases included PubMed, Scopus, and Cochrane Library. The Asthma Predictive Index (API) and lung function trajectories were analyzed. Results: Approximately 40-50% of infants hospitalized with bronchiolitis experience recurrent wheezing. Evidence suggests distinct phenotypes: RSV-induced bronchiolitis is largely associated with "transient early wheezing" due to smaller airway geometry, whereas Rhinovirus-induced wheezing, particularly in atopic infants, is a strong predictor of persistent asthma and allergic sensitization by school age. Conclusion: Post-bronchiolitis wheezing is a heterogeneous condition. Differentiating between transient sequelae and early-onset asthma is crucial for appropriate management. Children with Rhinovirus-induced severe bronchiolitis warrant closer follow-up for asthma prevention strategies.